2014
DOI: 10.4236/jwarp.2014.62014
|View full text |Cite
|
Sign up to set email alerts
|

Average Rainfall Estimation: Methods Performance Comparison in the Brazilian Semi-Arid

Abstract: Considering the rainfall's importance in hydrological modeling, the objective of this study was the performance comparison, in convergence terms, of techniques often used to estimate the average rainfall over an area: Thiessen Polygon (TP) Method; Reciprocal Distance Squared (RDS) Method; Kriging Method (KM) and Multiquadric Equations (ME) Method. The comparison was done indirectly, using GORE and BALANCE index to assess the convergence results from each method by increasing the rain gauges density in a region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…They also calculated the accuracy of the AAR on areas that lack density of rain gauge by using the PRISM (Parameter-elevation Regressions on Independent Slopes Model) method. Cheng et al [5] evaluated and augmented rain gauge network using geostatistical approach and Barbalho et al [28] compared the estimation techniques of AAR such as Thiessen polygon method, IDW (Inverse Distance Weighting), Kriging Method (KM), Multiquadric Equations Method (ME). According to Barbalho et al [28], TM, IDW and ME Method are to be shown with good performance to obtain AAR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also calculated the accuracy of the AAR on areas that lack density of rain gauge by using the PRISM (Parameter-elevation Regressions on Independent Slopes Model) method. Cheng et al [5] evaluated and augmented rain gauge network using geostatistical approach and Barbalho et al [28] compared the estimation techniques of AAR such as Thiessen polygon method, IDW (Inverse Distance Weighting), Kriging Method (KM), Multiquadric Equations Method (ME). According to Barbalho et al [28], TM, IDW and ME Method are to be shown with good performance to obtain AAR.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas KM, tested with two variograms models, had a not expected unstable behaviour. True mean areal rainfall and its distributions will always remain unknown variable even various techniques of AAR estimation exist [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the parametric model is a combination of deterministic and stochastic models. In the stochastic model, there are several methods used to calculate rainfall, including: arithmetic method, polygon, and comparison method [25], [26]. These three methods function for forecasting rainfall in an area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(USDA) to estimate the missing rainfall data by considering the reciprocal of the inverse of distances between the target station and the surrounding stations (Barbalho et al 2014). The formula of IDW method is as follows:…”
Section: Inverse Distance Weighting (Idw)mentioning
confidence: 99%